Heart rate and heart rate variability in infants during olfactory stimulation - Yuko Tsunetsugu; Keita Ishibashi (Taylor & Francis Group, 2019)
Background: Various plant odours have been shown to decrease heart rate and increase parasympathetic nervous activity. However, 'innate' autonomic responses without the influences of experience, assumptions and prejudices of odours remains unclear. Aim: To clarify changes in heart rate and heart rate variability in infants while presenting different components of plant odours. Subjects and methods: The study participants included 17 infants aged 1-3.5 months. Each infant was exposed to the odours of α-pinene, D-limonene and air (as a control) for 2 minutes after a 2-minute resting period without any odours. The intervals of heartbeat (R-R intervals) were recorded during this process. Results: Heart rate significantly decreased in response to the odour of limonene. Frequency analysis of heart rate variability revealed that the power value at 0.2 Hz was significantly higher during the odour presentation of limonene compared to the baseline and that at 0.1 Hz and 0.4 Hz was significantly lower during α-pinene presentation. Conclusion: Autonomic responses to specific natural odours may be partly shaped innately, while underlying physiological mechanisms may be different between infants and adults.